Metaverse magic: Unveiling the pedagogical potential and transformative effects on intercultural communication in English language teaching - Endro Dwi Hatmanto; Bambang Widi Pratolo; Mariska Intan Sari (Universitas Ahmad Dahlan, 2023)
The emergence of Metaverse, a three-dimensional virtual space that enables users to interact in computer-generated environments, has opened up new possibilities for language learning and instruction. This study explored the pedagogical potential and transformative effects of incorporating Metaverse environments in English language teaching, with a specific focus on intercultural communication. Drawing on theories such as social constructivism, intercultural communication, and autonomous language learning, this research investigated the impact of Metaverse on language acquisition, intercultural competence, and learner autonomy. The study employed a qualitative approach, including interviews with experts in Metaverse development and English language instructors. The findings revealed several pedagogical implications, including the promotion of immersive language learning experiences, enhanced interaction and collaboration, personalized learning opportunities, and increased motivation. Additionally, the study uncovered the positive impacts of Metaverse environments on intercultural communication and cultural understanding in English language learning. The research contributed to the understanding of how Metaverse could support language education and provides valuable insights for language teachers and students to optimize their language learning experience in virtual environments.